2016
DOI: 10.1007/s11356-015-5960-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of selenosulfate versus selenite in tumor cells depends on cell line and presence of amino acids

Abstract: Based on acute cytotoxicity studies, selenosulfate (SeSO3 (-)) has been suggested to possess a generally higher toxic activity in tumor cells than selenite. The reason for this difference in cytotoxic activity remained unclear. In the present study, cytotoxicity tests with human hepatoma (HepG2), malignant melanoma (A375), and urinary bladder carcinoma cells (T24) showed that the selenosulfate toxicity was very similar between all three tested cell lines (IC50 6.6-7.1 μM after 24 h). It was largely independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…In comparison with previous studies, Hinrichsen and Planer-Friedrich 18 reported that especially at short exposure times, selenite toxicity to HepG2 cells was remarkably low and with longer exposure times, selenite toxicity increased. In Hinrichsen and Planer-Friedrich’s 18 study, 5 µM selenite resulted in 87% CV after 24 h, while in the study of Zhang et al, 20 6 µM selenite resulted in 90% CV after 72 h. The difference in results could be attributed to different cell culture conditions. In addition, the results of this study showed that changes in Se supply to HepG2 cell line can alter the miRNA profile.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In comparison with previous studies, Hinrichsen and Planer-Friedrich 18 reported that especially at short exposure times, selenite toxicity to HepG2 cells was remarkably low and with longer exposure times, selenite toxicity increased. In Hinrichsen and Planer-Friedrich’s 18 study, 5 µM selenite resulted in 87% CV after 24 h, while in the study of Zhang et al, 20 6 µM selenite resulted in 90% CV after 72 h. The difference in results could be attributed to different cell culture conditions. In addition, the results of this study showed that changes in Se supply to HepG2 cell line can alter the miRNA profile.…”
Section: Discussioncontrasting
confidence: 64%
“…16,17 Experiments with human tumor cell lines are basic preclinical trials for anticancer drug permission. 18 In fact, the use of dietary antioxidants and micronutrients has been proposed for successful HCC management. 19 Due to the narrow concentration range between beneficial and toxic effects and a potential negative influence on healthy tissue, application of selenite in cancer treatment is still discussed quite controversially.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, selenate might be more effective than selenite under certain circumstances as described earlier, even in the same type of cancer albeit different cell lines [71,72]. Inorganic Se such as selenosulfate (SeSO 3 − ) was reported to have generally greater cytotoxic effects on cancer cells but was less toxic in healthy cells than selenite, depending on the cell types and the presence or absence of supplement amino acids that may affect the uptake of selenite [89]. Both SeSO 3 − and selenite might have the potential to work as a remedy against chemotherapy toxicity [76,84].…”
Section: Se-containing Compounds and Their Usage In Oncologymentioning
confidence: 99%
“…Previous work has shown that cellular susceptibility to selenite differs among cell lines [ 15 ]. However, no reasonable explanations for the specific susceptibility of the cell lines have been presented.…”
Section: Introductionmentioning
confidence: 99%